At Grips with Romans 5:1 - Lundahl, Kalle O. (Journal of ecumenical studies, 2024)
, precis:, The modern edition of the Greek New Testament, the Nestle-Aland, prints Romans 5:1 as follows: Δικαιωθέντες οὖν ἐκ πίστεως εἰρήνην ἔχομεν πρὸς τὸν θεὸν διὰ τοῦ κυρίου ἡμῶν Ἰησοῦ Χριστοῦ ("Therefore, being justified by faith, we have peace with God through our Lord Jesus Christ"). The main verb is ἔχομεν ("we have [peace]"). However, is this the right verb form? The person who copied the text (from an earlier, now lost manuscript) in the two fourth-century manuscripts, Sinaiticus and Vaticanus, wrote the hortative subjunctive ἔχωμεν ("let us have"). A later, correcting, hand changed it to the indicative ἔχομεν ("we have")—present in the Nestle-Aland. The subjunctive introduces an element of uncertainty about whether Christians (already) enjoy peace with God. This question relates to the doctrine of justification—one of the most divisive topics of the Reformation and the Counter-Reformation. The indicative variant supports the Lutheran side, while the subjunctive conforms to the Catholic viewpoint. Instead of the exclusive choice of one variant or the other, this essay proposes that future editions of the Greek New Testament print a neologism that combines both variants into one, ἔχôμεν ("let us have" and "we have"). M. C. Escher's lithograph Drawing Hands is used to show that the correcting and the original hands (in Sinaiticus and Vaticanus) are on the same level (in a tangled hierarchy). Finally, J. Derrida's neologism "otobiography" is used to demonstrate that the omicron and the omega are interwoven in Rom. 5:1.